Women Offender From Criminogenic Needs To Recidivism Risk - شيباني, هجيرة; بشقة, عزالدين (مجلة دراسات في سيكولوجية الانحراف, 2022)
The study aimed to identify the most important risk factors contributing to the commission of criminal behaviour and its recurrence, which are called criminogenic needs, and to reveal their relationship to the phenomenon of recidivism risk among women offenders, by analysing these criminogenic needs and determining their relationship to recidivism risk among women offenders. There is a relationship between the criminogenic needs and the recidivism risk of woman offender, as it included (anti-social personality, criminal attitudes, social support, addiction, low educational level, the absence of participation in recreational and social activities), and it is closely related to the phenomenon of recidivism risk among the woman offender, which can be Reliance on it by specialists in the development of programs for their interventions.